Political Education for Beginner Voters Through Civics Learning to Increase Awareness of Political Hoaxes - Arif Sobirin Wibowo,; Apeles Lexi Lontoh,; Ida Bagus Weda Wigena, (Technium Social Sciences Journal, 2023)
Beginner voters tend to change easily in terms of believing in something, especially in elections and politics, so they may become a favorite target for prospective candidates and political parties in getting votes. If novice voters do not have sufficient knowledge about politics, they will be easily influenced and will be easily influenced by hoaxes on social media, therefore political education is needed that is integrated into Civics subjects. This article belongs to the literature study which comes from books and journals. One way that can be done to educate prospective voters, especially first-time voters, to take part in elections so that they are increasingly aware of hoaxes and not affected by them is by increasing understanding through political education in Civics learning. Political education is not directly in the curriculum or learning but is integrated into lesson plans through Civics learning that is adapted to the independent learning curriculum. So that later political education carried out through PPKn learning can increase the vigilance of novice voters against political hoaxes on social media to produce qualified and responsible first-time voters, so that in the future it is hoped that the character of voters will be formed in honest and fair general elections so that the possibility of someone becoming a good citizen will be even greater.